ABIOTIC AND BIOTIC FACTORS AFFECTING THE OCCURRENCE OF THRIPS ON LOTUS FLOWERS - S BUMROONGSOOK (My University, 2018)
Frankliniella schultzei Trybom and Scirtothrips dorsalis Hood are two important insect pests of lotus flowers (Nulumbo nucifera Gearn).Both are active throughout the year and are difficult to control during pre-and post-harvest management.This study is focused on factors that influence the relationship among the thrips, their host plants and abiotic factors.Therefore, the distribution of these thrips species within lotus flowers of different flower ages was assessed using randomly sampling from commercially growing areas in Bangkok, Thailand and investigated thrips abundance on these flowers every week from April to September, 2016.The results revealed that there was a higher thrips population on older lotus flowers.S. dorsalis was much more abundant in summer than in the rainy season.It was found mainly on the pedicel and the outer corolla of the flowers.In the summer and rainy season, F. schultzei occurred most often and were found on the distal parts of lotus petals and pollen areas.Hindu lotus and East Indian lotus could support more of F. schultzei and S. dorsalis than Album Plenum and Roseum Plenum.The correlation among abiotic factors (temperature, amount of rainfall and relative humidity) and population fluctuations of S. dorsalis and F. schultzei was assessed.The studies showed a positive correlation of temperature (r = 0.7918) and a negative correction of relative humidity (r = -0.7588) to population of S. dorsalis but no relation with amount of rainfall (r = 0.0260).Whereas, there were non-significant correlations among F. schultzei and temperature (r = 0.43650, relative humidity (r = -0.2113)and rainfall (r = -0.4164).Interactions between different temperatures, relative humidity and rainfall effects on the abundance of the thrips were seen here.Both fundamental and applied perspectives will provide better understanding the thrips population abundance, and help to develop management plans for thrips control.
Keywords: Biotic component; Flowering Plant Growth and Cultivation